Choroidal Melanoma Treated with Linear Accelerator-based Hypofractionated Stereotactic Radiotherapy: First Case of Globe Conservation in Uveal Melanoma from the Philippines - Raymund V. Tanchuling, MD; Andrei P. Martin, MD (Philippine Journal of Ophthalmology)
Objective: This is a case report of a 60-year-old woman with a juxtapapillary choroidal melanoma who underwent globe-sparing treatment using linear-accelerator (LINAC)-based hypofractionated stereotactic radiotherapy (FSRT).